The first record of a fly of the family Milichiidae (Diptera) interacting with an ant of the genus Polyrhachis Smith, 1857 (Hymenoptera: Formicidae) - Kalsum Yusah; Tom Fayle (Biodiversity Data Journal, 2014)
Flies in the family Milichiidae are often myrmecophilic. We document the first record of a fly from this family interacting with an ant of the genus Polyrhachis. In lowland riparian rainforest in Sabah, Malaysia, we observed a female of the genus Milichia following an ant of the species of P. illaudata, and repeatedly attempting to make close contact. Our observation suggests that the dipteran may have been attempting to feed kleptoparasitically from the Polyrhachis worker, since members of this ant genus often feed on liquid carbohydrate-rich food resources. This is the first time an interaction has been observed between a fly of this family and an ant of this widespread old world tropical genus.